Efeito da heterogeneidade ambiental na predação de girinos de Scinax fuscovarius e Physalaemus cuvieri por larvas de Odonata - Fulan, João Ânderson; Almeida, Silvio César [UNESP] (Universidade Estadual de Maringa, 2010)
The objective of this work were to analyze the effect of predation by Odonata naiads on two amphibian species with distinct habits - benthic and mid-water -and to verify whether the presence and architecture of macrophytes can mediate this interaction. All tadpoles and Odonata larvae were captured in a temporary pond. Sixteen tanks were used for three different treatments: Pistia, Salvinia and no macrophytes. Ten tadpoles of each species and two Odonata larvae were placed in each tank. The survival of tadpoles according to treatments was assessed through analysis of repeated measures. We concluded that the survival of P. cuvieri and S. fuscovarius tadpoles was not affected by the presence and architecture of the macrophytes (Pistia and Salvinia) or by their behavior.
Effect of the spatial heterogeneity on the predation of Scinax fuscovarius and Physalaemus cuvieri tadpoles by Odonata larvae
Keywords: Macrophyte; Odonata; Predation; Tadpole; Amphibia; animal behavior; animal experiment; aquatic species; benthos; controlled study; ecosystem; frogs and toads; habitat; macrophyte; naiad (nymph); nonhuman; Physalaemus cuvieri; Pistia; plant; pond; predation; predator prey interaction; Salvinia; Scinax fuscovarius; spatial heterogeneity; species distribution; survival; tadpole; tank; Najas